The Influence of Work Discipline, Work Motivation, Work Ethic, and Work Environment on Employee Performance at the Kartini Open University Service Center in Rembang - Alifuddin, Andreas; Utami, Intiyas; Lestari, Etty Puji (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study is entitled “The Effect of Work Discipline, Work Motivation, Work Ethic, and Work Environment on Employee Performance at the Kartini Open University Service Center in Rembang” with all employees at the institution as the research object. The purpose of this study is to examine the influence of work discipline, work motivation, work ethic, and work environment on employee performance, both partially and simultaneously. The study uses a quantitative method with a survey approach, and data are analyzed using the Partial Least Squares (PLS) model through the SmartPLS application. The results of the study indicate that work discipline, work motivation, and work ethic have a positive but insignificant influence on employee performance, while the work environment is proven to have a positive and significant influence on performance. These findings indicate that the work environment has an important role in improving performance, while other variables need to be strengthened through integrated managerial strategies, such as improving the provided system, leadership training, and developing a work culture that is in accordance with organizational values. These results are expected to be a basis for management in designing policies to improve employee performance continuously to achieve more optimal work effectiveness and productivity.